1991
DOI: 10.1002/aoc.590050210
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of organotin compounds from poly(vinyl chloride) (PVC) material

Abstract: The release of mono-and di-butyltin species (MBT and DBT) in water after leaching of five different poly(viny1 chloride) (PVC) materials was investigated under mild conditions over a period of one month in batch reactor systems. Results showed that inorganic tin, MBT and DBT compound were released from the material tested under experimental static leaching conditions. The total amount of inorganic tin and organotin compounds observed upon leaching varied considerably from one PVC material to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…In the presence of metallic lithium a mixture containing mainly tributyltin chloride/bromide was obtained. Treatment of this mixture with butylmagnesium bromide (1) gave tetrabutylstannane (3). Further experimentation demonstrated that the conversion of tributyltin halide to 3 could be achieved by reaction with butyl bromide (9) and that this product was of significantly higher purity than that obtained from reaction of tributyltin halide with 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of metallic lithium a mixture containing mainly tributyltin chloride/bromide was obtained. Treatment of this mixture with butylmagnesium bromide (1) gave tetrabutylstannane (3). Further experimentation demonstrated that the conversion of tributyltin halide to 3 could be achieved by reaction with butyl bromide (9) and that this product was of significantly higher purity than that obtained from reaction of tributyltin halide with 1.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition to being a known product of the breakdown and metabolism of tributyltin (TBT), which for many years was a major antifouling agent in marine paints, dibutyltin is a stabilizer in polyvinyl chloride pipes and thus has the potential for leaching into drinking water. 3 DBT binds tenaciously to some tissues and other matrices thereby increasing its probability for persistence both in living organisms and in the environment. The toxic effects of organotins have been known 4 for many years and have been the subject of considerable research.…”
Section: Introductionmentioning
confidence: 99%
“…33 Polytetrafluoroethylene (PTFE) as the container material was shown to cause species loss, most probably owing to the porosity of this material. 34−36 Poly(vinyl chloride) (PVC) bottles must be ruled out as container material, because PVC contains TBT for UV stabilisation which has been found to leach out of PVC containers 37 and also from PVC tubes used for water supply. 38 Several reviews on this topic can be found.…”
Section: Water (Aqueous) Samplesmentioning
confidence: 99%
“…Due to its widespread use in consumer and agricultural products, DBT has been detected in surface water and drinking water at levels of 2 ppb and 53 ng/L, mainly from leaching out of PVC piping (Jones-Lepp et al, 2004;Sadiki and Williams, 1999). PVC piping is used extensively across the United States and other countries to transport water to/from homes and research has shown that DBT continuously leaches from PVC pipes for an indefinite period of time (Forsyth and Jay, 1997;Quevauviller et al, 1991). The presence of organotins in Canadian and European drinking water (Sadiki and Williams, 1999), prompted the European countries to propose banning the use of (United Kingdom, 1995-1996 PVC.…”
Section: Introductionmentioning
confidence: 99%